In vitro activities of Ro 17-2301 and aztreonam compared with those of other new beta-lactam antibiotics against clinical isolates of Pseudomonas aeruginosa. - Ng, W W (1985)
The in vitro activities of Ro 17-2301 and aztreonam against 191 Pseudomonas aeruginosa isolates were compared with those of five other beta-lactam antibiotics. Both compounds showed activities comparable to that of ceftazidime and were bactericidal. They were as effective against gentamicin-or carbenicillin-resistant isolates as against susceptible ones.